Carious lesions recurrence in children with developmental disabilities: a longitudinal study - Lia Silva de CASTILHO; Ivana Márcia Alves DINIZ; Bruno Pereira dos Reis SANTOS; Frederico Santos LAGES; Alex Júnio Silva da CRUZ; Mauro Henrique Nogueira Guimarães ABREU (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract This study investigated the factors associated with new carious lesions in one-to five-year-old children with developmental disabilities. This was a retrospective cohort that evaluated 64 dental charts of individuals with caries or fillings in their first dental appointment. The dependent variable was the occurrence of a new carious lesion or restoration. Gender, age, mother's education, sugar consumption, oral hygiene, mouth breathing, reports of xerostomia, gingival status, use of psychotropic drugs, use of asthma drugs, history of asthma, bronchitis, reflux or seizures and having at least one sibling were covariates. Cox proportional hazards regression model was used to estimate the raw and adjusted hazard ratios with their respective 95% confidence interval. The average time that individuals remained free of dental caries/restoration was 79.49 months (95%CI: 64.37 to 92.61). Increase in sucrose consumption increased the rate of caries recurrence (HR = 1.16; 95%CI: 1.04 to 1.30). Individuals who had poor oral hygiene had higher rate of new dental caries (HR = 3.88; 95%CI: 1.22 to 12.37) compared to those with good oral hygiene. The presence of mouth breathing decreased the rate of recurrence of the disease when compared to the nasal breathing (HR = 0.32; 95%CI: 0.15 to 0.70). Oral health-related behaviors and nasal respiration influenced the rate of dental caries recurrence in individuals with developmental disabilities.